Emergency Radiology: Evolution, Current Status, and Future Directions. Issue 4 (November 2022) - Li, David; Basilico, Raffaella; Blanco, Ana; Calli, Cem; Dick, Elizabeth; Kirkpatrick, Iain D. C.; Nicolaou, Savvas; Patlas, Michael N.
Emergency Radiology is a clinical practice and an academic discipline that has rapidly gained increasing global recognition among radiology and emergency/critical care departments and trauma services around the world. As with other subspecialties, Emergency Radiology practice has a unique scope and purpose and presents with its own unique challenges. There are several advantages of having a dedicated Emergency Radiology section, perhaps most important of which is the broad clinical skillset that Emergency Radiologists are known for. This multi-society paper, representing the views of Emergency Radiology societies in Canada and Europe, outlines several value-oriented contributions of Emergency Radiologists and briefly discusses the current state of Emergency Radiology as a subspecialty.